Dollars, Debt, and International Financial Institutions - Yeyati, Eduardo Levy (World Bank, 2012)
Financial dollarization is increasingly seen as a concern because of its tendency to contribute to financial crises and output volatility. As a result the debate on financial dollarization has shifted in favor of a more proactive stance on dedollarization. While often neglected, lending from international financial institutions is an important source of financial dollarization in emerging economies and must be considered in any dedollarization strategy. This article revisits old and new arguments in favor of international financial institution lending in the local currency and argues that any such initiative should rely, at least initially, on demand from residents seeking stable returns in units of the local consumption basket but who are reluctant to take on sovereign risk. Superior enforcement capacity enables international financial institutions to intermediate these savings, currently invested in dollarized foreign assets, back into the local economy. The international financial institutions can offer investment-grade local currency bonds and use the proceeds to dedollarize their own lending to noninvestment-grade countries, thereby reducing financial dollarization and fostering the development of local currency markets.